Multi-location anywhere astronomy paradigm. (12th August 2020) - Periola, A.A.; Akinyemi, L.A.; Sesham, S.
It is challenging for capital-constrained astronomy organisations to construct telescopes and they consider converting unused satellite earth stations to telescopes. This conversion strategy is not sustainable due to the limited number of available unused satellite earth stations. This paper proposes a synergy between radio astronomy and satellite-television broadcasting to address this challenge. The paper proposes a software-defined radio-enabled a multi-mode satellite-television terrestrial telescope with an associated set-top box. The proposed solution provides all-round access to telescopes for astronomy observations at an increased number of locations. The proposed solution also enhances subscriber ability to enjoy free to air satellite television by reducing the costs of acquiring a subscriber decoder entity. The performance benefit of the proposed solution is investigated using system acquisition costs, angular resolution, and decoder entity acquisition costs. The proposed solution reduces telescope acquisition cost and decoder entity acquisition costs by 32.5% and up to 83.9% on average respectively. The angular resolution is enhanced by up to 27.4% on average.